2011
DOI: 10.1111/j.1365-2222.2011.03778.x
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase IV (DPP4) deficiency increases Th1-driven allergic contact dermatitis

Abstract: The up-regulation of CD26 in atopic dermatitis represents a new finding, which has also been seen in other inflammatory skin diseases. However, tissue expression of CD26/DPP4 in immunological skin response can either be beneficial or aggravating, depending on a possible Th1/Th2 shift. This might have consequences for humans suffering from diabetes mellitus treated by DPP4 inhibitors, who have eczematous skin diseases as a co-morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 46 publications
0
30
0
1
Order By: Relevance
“…Treatment with DPP4 inhibitors reduced leukocyte counts and, in particular, T cell and B cell infiltration in 2 murine models of SSc, both of which are centrally involved in the pathogenesis of SSc (1,46). Indeed, DPP4 has been shown to regulate Th2 polarization and regulate B cell activation (47)(48)(49)(50). Despite the potent effects on B cell and T cell infiltration into fibrotic tissues, our bone marrow transplantation experiments actually demonstrated that the profibrotic effects of DPP-4 required that DPP-4 be predominantly expressed in tissue-resident cells such as fibroblasts.…”
Section: Discussionmentioning
confidence: 81%
“…Treatment with DPP4 inhibitors reduced leukocyte counts and, in particular, T cell and B cell infiltration in 2 murine models of SSc, both of which are centrally involved in the pathogenesis of SSc (1,46). Indeed, DPP4 has been shown to regulate Th2 polarization and regulate B cell activation (47)(48)(49)(50). Despite the potent effects on B cell and T cell infiltration into fibrotic tissues, our bone marrow transplantation experiments actually demonstrated that the profibrotic effects of DPP-4 required that DPP-4 be predominantly expressed in tissue-resident cells such as fibroblasts.…”
Section: Discussionmentioning
confidence: 81%
“…CD26/DPP4 appears to play a role in a number of other diseases (see Table ). In atopic dermatitis, CD26/DPP4 expression was up‐regulated in the skin biopsies of patients compared with healthy controls, as well as in both models of contact hypersensitivity . In psoriasis, reduced expression of CD26/DPP4 on CD8 + T cells has been observed .…”
Section: Involvement Of Cd26/dpp4 In Pathologymentioning
confidence: 99%
“…CD26 enzymatic activity downmodulates the biological function of most of these chemokines and cytokines (Table 3). Consistent with this observation, it has been found that CD26 inhibitors can enhance some in vivo immune responses depending on the dose, application route, timing or predominant Teff subset [45,169], which could be explained by the presence of offtarget effects as well [25,170]. However, animal models of rheumatoid arthritis [93], multiple sclerosis [171] and inflammatory bowel disease [172] in CD26 KO mice do support an immunosuppressive role of both CD26 and DPP4 activity.…”
Section: Inhibitory Functions Of Both Membrane and Soluble Cd26 On Asmentioning
confidence: 58%